Odpowiedzi

  • Użytkownik Zadane
2009-09-17T19:54:43+02:00
A) (2x+3)do potęgi2(2x-3) do potęgi2 =
= (4X²+6X+9)(4X²-6X+9)=
= 16X⁴-24X³+36X²+24X³-36X²+54X+36X²-54X+81=
=16X⁴+36X²+81

b) (2xdo potęgi 3 +x do potęgi 2)do potęgi 2 (x do potęgi 2 -2x do potęgi 3) do potęgi 2 =
= (4x do 9+4x do6 +x⁴)(x⁴-4x do6+4x do9)=
=4xdo13+16xdo15+16xdo18+4xdo10-16xdo12+16xdo15+xdo8-4xdo10+16xdo13=
=20xdo13+16xdo18-16xdo12=
= 16xdo18+20xdo13-16xdo12
2009-09-17T21:43:45+02:00
A) (2x+3)²(2x-3)² = (4x²+12x+9)(4x²-12x+9) = 16x⁴-48x³+36x²+48x³-144x²+108x+36x²-108x+81 = 16x⁴-72x²+81


b) (2x³+x²)²(x²-2x³)² = (4x⁶+4x⁵+x⁴)(x⁴-4x⁵+4x⁶) = 4x¹⁰-16x¹¹+16x¹²+4x⁹-16x¹⁰+16x¹¹+x⁸-4x⁹+4x¹⁰ = 16x¹²-8x¹⁰+x⁸